2019
DOI: 10.1016/j.abb.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Bm-iAANAT3: Expression and characterization of a novel arylalkylamine N-acyltransferase from Bombyx mori

Abstract: The arylalkylamine N-acyltransferases (AANATs) are enzymes that catalyze the acyl-CoA-dependent formation of N-acylarylalkylamides: acyl-CoA + arylalkylamine → N-acylarylalkylamides + CoA-SH. Herein, we describe our study of a previously uncharacterized AANAT from Bombyx mori: Bm-iAANAT3. Bm-iAANAT3 catalyzes the direct formation of N-acylarylalkylamides and accepts a broad range of short-chain acyl-CoA thioesters and amines as substrates. Acyl-CoA thioesters possessing an acyl chain length >10 carbon atoms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…The decrease in the K M values from acetyl-CoA to decanoyl-CoA is approximately matched with a decrease in the k cat values; thus, we find little change in the k cat /K M values. These data are consistent with our earlier work on other iAANATs showing that long-chain acyl-CoAs are inhibitors, competitive vs. acetyl-CoA [19,22,24]. These data suggest that the amine binding pocket is blocked if the acyl chain is beyond a certain length.…”
Section: Characterization Of Acyl-coa Substrates For Recombinant Tcaanat1bsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease in the K M values from acetyl-CoA to decanoyl-CoA is approximately matched with a decrease in the k cat values; thus, we find little change in the k cat /K M values. These data are consistent with our earlier work on other iAANATs showing that long-chain acyl-CoAs are inhibitors, competitive vs. acetyl-CoA [19,22,24]. These data suggest that the amine binding pocket is blocked if the acyl chain is beyond a certain length.…”
Section: Characterization Of Acyl-coa Substrates For Recombinant Tcaanat1bsupporting
confidence: 92%
“…This is consistent with the understanding that insect AANATs (iAANATs) perform a variety of roles, including cuticle sclerotization, biogenic amine removal, and fatty-acid amide biosynthesis [14][15][16][17][18]. Much effort has been put into identifying and characterizing these enzymes and the panel of substrates each utilizes, from both an acyl-CoA donor and amine acceptor perspective [7,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionsupporting
confidence: 72%
“…Of the GNATs that have had their kinetic mechanism experimentally determined, these enzymes overwhelmingly favor a direct transfer/sequential mechanism regardless of the identity of their acceptor substrate classification. Indeed, a large number of kinetic studies have shown that Gcn5/pCAF histone N- acetyltransferases (HATs) ( Jiang et al, 2012 ), arylalkylamine N- acetyltransferases (AANATs) ( Dempsey et al, 2014 ; Battistini et al, 2019 ), aminoglycoside N- acetyltransferases (AACs) ( Vetting et al, 2008b ), spermidine/spermine N- acetyltransferases (SSATs) ( Bewley et al, 2006 ; Filippova et al, 2015 ), and GNATs with unknown native substrates ( Majorek et al, 2017 ; Reidl et al, 2017 ) all utilize some form of a direct transfer mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed final step in the biosynthesis of the gymnastatin N, a fungal cytotoxic metabolite, is the reaction between d -tyrosine and (2 E ,4 E ,6 R )-4,6-dimethyl-2,4-dodecadienoyl-CoA, as catalyzed by an acyltransferase ( Tong et al, 2021 ). We have identified N -arylalkylamine N -acyltransferases (AANATs) that accept long-chain acyl-CoA thioesters and arylalkylamines that are related to the aromatic amino acids, like histamine, phenethylamine, tyramine, and tryptamine, but these enzymes will not utilize the aromatic amino acids as substrates ( Dempsey et al, 2014 ; Dempsey et al, 2015 ; Battistini et al, 2019 ).…”
Section: Biosynthesismentioning
confidence: 99%